The life table of Indian meal‐moth, Plodia interpunctella (Hübner) (Lepidoptera: Phycitidae) from two different warehouses in Malaysia - Muhamad Noor Syafiq Omar,; Abdul Hafiz Ab Majid, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Plodia interpunctella were collected from two warehouses in Penang, Malaysia namely Ray Synergy (RYA) and Lorong Perusahaan (CCW). There was a significant difference (F = 8.470; P<0.05) in the duration of total development time of different stages from larva to the adult for P. interpunctella reared in the laboratory from the RYA warehouse. The information on stored product insect pest diversity, environmental factors, and life cycle in rice storage warehouses is very important to implement effective pest management and controlling insect pest infestation in stored rice grains.